Pengaruh Model Pembelajaran dan Kemampuan Gerak Tari Terhadap Kecerdasan Emosional Anak Usia Dini - Elindra - Yetti (LP2M ISBI Bandung, 2012)
ABSTRACT The objectives and targets in this study was to determine the effect of learning models and the ability dance movement toward early childhood emotional intelligence. Emotional intelligence is the ability to recognize emotions, managing emotions, motivating oneself, recognizing emotions of others (empathy) and the ability to build relationships (cooperation) with other people. The research method used in this study is the experimental method. In the experiment, there are two groups of subjects namely experimental group and control group. Because the research hypothesis is the hypothesis of interaction, then the most appropriate design is factorial desig;n, factorial design used was 2 x 2 fac- torial design. Treatment variable is the learning model, are considered to be a model student center and a teacher center, while the variable attribute is the ability to dance, dance movement capabilities are classified into high and low dance movement. The results showed that there are significant learn- ing model and the ability to dance on the emotional intelligence of young children. The implications obtained in this study that the experience of dance movement with a model of student learning center is an important cornerstone in the development of emotional intelligence since early childhood. Based on the best learning implications Art Culture and Skills should give students experience in dance movement. With that in mind, the potential students will be able to develop optimally. Kata Kunci: Learning model, dance movement, and emotional intelligence